2019
DOI: 10.1093/ckj/sfz030
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial fat, cardiovascular risk factors and calcifications in patients with chronic kidney disease

Abstract: Background Epicardial adipose tissue (EAT) exerts cardiopathogenic effects, but the independent association between EAT and cardiovascular (CV) calcification in patients with chronic kidney disease (CKD) remains controversial. We therefore assessed the association between EAT, CV risk factors and CV calcifications. Methods 257 patients with CKD Stage 3 and/or overt proteinuria underwent quantification of EAT, coronary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Computed tomographic imaging was performed on a Dual Source CT scanner (SOMATOM Definition Flash or Force; Siemens), as previously described. 14 With a median follow-up time of 4.4 years, 41 of 78 patients agreed or were available for a second computed tomographic scan during the second CARVIDA visit in 2019 and 2020.…”
Section: Cardiovascular In Depth Assessment (Carvida) Cohortmentioning
confidence: 99%
“…Computed tomographic imaging was performed on a Dual Source CT scanner (SOMATOM Definition Flash or Force; Siemens), as previously described. 14 With a median follow-up time of 4.4 years, 41 of 78 patients agreed or were available for a second computed tomographic scan during the second CARVIDA visit in 2019 and 2020.…”
Section: Cardiovascular In Depth Assessment (Carvida) Cohortmentioning
confidence: 99%
“…A meta-analysis of nine studies involving over 3500 patients revealed a link between increased EAT volume and CAD [ 11 ], as well as a link between increased EAT volume and high-risk coronary plaque formation [ 25 ]. EAT was discovered to be an independent risk factor for CVD in a meta-analysis of over 40,000 patients, and EAT volume was also linked to coronary artery calcification and myocardial ischemia [ 27 ]. According to recent research, EAT is an independent predictor of coronary events and left ventricular dysfunction, but visceral adipocyte tissue accumulation is not an independent risk factor for cardiovascular events [ 28 , 29 , 30 , 31 ].…”
Section: The Relationship Between Epicardial Adipose Tissue and Cardi...mentioning
confidence: 99%
“…Dyslipidemia is another well-known traditional risk factor for cardiovascular disease. EAT was found to be inversely correlated with HDL cholesterol and positively correlated with LDL cholesterol and TG in studies examining the relationship between cholesterol levels and CVH and EAT [ 27 , 30 , 44 , 52 , 53 ].…”
Section: The Relationship Between Epicardial Adipose Tissue and Cardi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with chronic kidney disease (CKD) are at high risk of cardiovascular morbidity and mortality [1,2]. Aortic valve calcium (AVC) has been reported to occur 10-20 years earlier in CKD patients with a higher prevalence (28-55%) than that reported in the general population [3][4][5][6][7][8]. The association of cardiac valve (mitral and aortic) calcification and clinical outcomes has been studied in patients with end-stage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%